The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1161/01.hyp.21.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide and angiotensin II in the regulation of sympathetic nerve activity in spontaneously hypertensive rats.

Abstract: This study evaluated the actions of nitric oxide on the blood pressure and renal sympathetic nerve activity responses produced by angiotensin II (Ang II) blockade in conscious spontaneously hypertensive rats. Two days after implantation of electrodes, we measured mean arterial pressure, heart rate, and renal sympathetic nerve activity. Baroreceptor reflex function was assessed with a logistic function curve; the maximum slope of the curve estimated the baroreceptor reflex gain. Data were obtained in rats given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
2

Year Published

1994
1994
2005
2005

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 22 publications
4
46
1
2
Order By: Relevance
“…Our results demonstrate that the cyclo-oxygenase inhibitor, diclofenac (a) had no effect on the basal values of blood pressure and regional vascular resistances, and (b) (Tesfeimariam et al, 1987;1989;Sakuma et al, 1992;Vo et al, 1992;Toda et al, 1993;MacLean et al, 1994), and conversely NO synthase inhibition has been shown to increase sympathetic nerve activity (Sakuma et al, 1992;Harada et al, 1993;Kumagai et al, 1993;Toda et al, 1993;Zanzinger et al, 1994). The mechanisms by which NO appears to interact with the sympathetic nervous system comprise a reduction of the central sympathetic tone (decrease in peripheral sympathetic nerve activity) and an inhibition of its peripheral vasoconstrictor effects.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Our results demonstrate that the cyclo-oxygenase inhibitor, diclofenac (a) had no effect on the basal values of blood pressure and regional vascular resistances, and (b) (Tesfeimariam et al, 1987;1989;Sakuma et al, 1992;Vo et al, 1992;Toda et al, 1993;MacLean et al, 1994), and conversely NO synthase inhibition has been shown to increase sympathetic nerve activity (Sakuma et al, 1992;Harada et al, 1993;Kumagai et al, 1993;Toda et al, 1993;Zanzinger et al, 1994). The mechanisms by which NO appears to interact with the sympathetic nervous system comprise a reduction of the central sympathetic tone (decrease in peripheral sympathetic nerve activity) and an inhibition of its peripheral vasoconstrictor effects.…”
Section: Discussionmentioning
confidence: 55%
“…It appears from our study that losartan decreases blood pressure and regional vascular resistances in the pithed SHR which indicates either that AII contributes to the vascular tone in this preparation, or that losartan administration results in the release of vasodilator agents, among which NO (Cachofeiro et al, 1992; Kumagai et al, 1993;Sudhir et al, 1993) and PGs (Jaiswal et al, 1991;Catalioto et al, 1994) have previously been proposed as candidates. Our results also show that losartan significantly reduces or even abolishes the systemic pressor and renal and muscular vasoconstrictor responses elicited by electrical stimulation of the spinal cord but does not affect the simultaneously induced tachycardia, thus confirming the vascular selective sympathoinhibitory effects of the drug (Moreau et al, 1993).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Pretreatment with L-arginine prevented the late increase in RSNA suggesting that the potentiating effects of L-NMMA on sympathetic activity were due specifically to inhibition of NO synthesis. Other investigators have also shown increases in renal 45 and cardiac sympathetic nerve activity 46 during systemic NOS inhibition when baroreflex activation was prevented. Conversely, in baroreceptor intact rabbits, stimulation of NO synthesis with intravenous L-arginine caused a decrease in cervical sympathetic nerve activity and RSNA despite a fall in blood pressure.…”
Section: Nitrergic Modulation Of Sympathetic Nervous Activitymentioning
confidence: 88%
“…Some studies have suggested that NO inhibits baroreceptor-RSNA gain, as evidenced by an increase in reflex gain during acute systemic NOS inhibition. 45,49,61 However, a number of studies have failed to show any influence of NO on the reflex control of sympathetic activity. 47,62 This inconsistency is only partially explained by species differences or the effect of anaesthetics.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%